PENGARUH PELATIHAN DAN PENGEMBANGAN KARIER TERHADAP PRODUKTIVITAS KERJA PEGAWAI MELALUI VARIABEL MEDIASI MOTIVASI - Ariyanarti, Ria Dwi; Rosidi, Rosidi; Muda, Navi (Buletin Studi Ekonomi; VOLUME.28.NO.02.TAHUN.2023, 2025)
Reforming the quality of employees (human resources) is part of government reform in order to lead to the achievement of good governance. Efforts can be made through a performance management system, which is not only on staff but is comprehensive from leadership level employees to employees at the operational level. The purpose of this study was to analyze the direct and indirect effects of training and career development on work productivity through motivation as a mediating variable in employees of the Population and Civil Registration Office of Mojokerto Regency. This research method uses explanatory quantitative type. Respondents in this study were all employees totaling 52 taken by census / saturated sampling, using statistical analysis, namely SEM-PLS. The results showed that training had no effect on motivation, career development had an effect on motivation, motivation and career development had an effect on work productivity, training had no effect on work productivity, motivation could not mediate the effect of training on work productivity, and motivation could mediate the effect of career development on work productivity.